Synthesis of Augmented Reality Use in the Development of English Language Writing Skills - Al-Hazmi, Hadeel Hassan; Al-Najami, Mai Mohammed Lutfi (Journal of Curriculum and Teaching Methodology, 2023)
Learning English and mastering its skills is one of the most critical priorities of the current times, as educational policies give great importance to providing students with the skills necessary to learn English, especially the skill of writing, and in the shadows witnessed by the educational system of developments that forced it to keep pace with the technological revolution and employ modern digital technologies, the most important of which are augmented reality technologies because of their enjoyment, fun and attractiveness to the educational process, and its focus on students and its promotion of the self-learning process, and in light of this, The current study aimed to identify the role of augmented reality in the development of the English language. Writing skills of primary school students through theoretical literature and the researcher used the descriptive method. The study found that augmented reality technologies enhance students' motivation to learn and increase the processes of attention and concentration, thus increasing the level of cognitive achievement, and that the techniques of scientific application of writing skills contribute. Therefore, they focus on the learner and enhance self-learning among students, and thus they help learners develop thinking skills, enhance learners' independence, help learners feel more confident, increase learners' motivation to learn writing skills, and reduce obstacles to learning writing skills.
Keywords: enhanced reality; English writing skills